KEPADATAN KOLONI SEMUT HITAM (Dholichoderus thoracicus Smit) PADA PERTANAMAN KAKAO DAN CENGKEH DI NAGARI SELAYO KABUPATEN SOLOK - Yunelki, Mutia; Jasmi, Jasmi; Fitriani, Vivi (STKIP PGRI Sumbar, 2014)
ABSTRACT Dolichoderus Thoracicus is controller agency of involved that is efficient to prevent a pest. It is one of natural enemies that can be used to prevent Helopeltis. Then, Dolichoderus Thoracicus is a kind of ant that is part of plantation agro-ecosystem in Indonesia. The aim of this research is to know the density of Dolichoderus Thoracicus by character; the nest on Kakao and Clove plant at Nagari Salayo Kabupaten Solok. This research is started from February 11th 2014 until February 14th 2014. Then, in this research, the researcher used census method by kept a close watches on and calculated the Dolichoderus Thoracicus nest directly those are found at research site. It is by calculated the quantity of the nest, measure diameter of the tree, calculated the quantity of the branch, measure the high of nest, calculated the quantity of nest leaf, and measure long and wide of nest. Based on the result of this research, the researcher found the greatest quantity of the density of Dolichoderus Thoracicus at clove plant 1.34 colonies, and the lower quantity at Kakao plant 0.92 colony. The researcher found the nest on diameter of tree 5-10 cm has145 quantity of nest. The greatest of having a nest is found at 1st -3rd of branch have 104 nests and1st -5th branch have131 nest. The greatest nest high found at 1-2 meter from the earth has 164 nests. The quantity of leaf as area of having nest is 1-2 leafs and have 105 nests. Then, the greatest nest long is between 11- 20 cm by quantity of nest 101 and the greatest leaf wide is between 6-10 cm by quantity of nest 126. In conclusion, the researcher found the density of Dolichoderus Thoracicus at Kakao plant more than at clove plant